Euglycemic Diabetic Ketoacidosis after Discontinuing SGLT2 Inhibitor - Mohamed Alhemeiri; Eiman Alseddeeqi (Case Reports in Endocrinology)
Background. Sodium glucose cotransporter-2 (SGLT2) inhibitors have been proven to be very effective in the management of type II diabetes. These medications can cause adverse drug reactions such as genital mycotic infections. Another critical adverse drug reaction is euglycemic diabetic ketoacidosis (EDKA) under the setting of other contributing risk factors for developing diabetic ketoacidosis. Case Presentation. We report a case of a 45-year-old gentleman with type 2 diabetes mellitus on empagliflozin, metformin, and glimepiride who presented with abdominal pain, fatigue, and vomiting. Of note, he started a ketogenic diet three days before his presentation and self-stopped his antidiabetic medications two days before his presentation. The patient was found to have euglycemic diabetic ketoacidosis and was treated as per the protocol. He was discharged on metformin and pioglitazone. Two weeks following discharge, canagliflozin was added. Conclusion. Euglycemic diabetic ketoacidosis could still be precipitated despite discontinuation of SGLT2I under a ketogenic diet. Discussion related to the initiation of a ketogenic diet should occur between the care provider and the patient.